2020
DOI: 10.1371/journal.pone.0225861
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemorophylaxis policy for AIDS-immunocompromised patients on emergence of bacterial resistance

Abstract: Chemoprophylaxis (antibiotic prophylaxis) is a long relied-upon means of opportunistic infection management among HIV/AIDS patients, but its use represents an evolutionary tradeoff: Despite the benefits of chemoprophylaxis, widespread use of antibiotics creates a selective advantage for drug-resistant bacterial strains. Especially in the developing world, with combined resource limitations, antibiotic misuse, and often-poor infection control, the emergence of antibiotic resistance may pose a critical health ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Both the emergence of antibiotic resistance and the vulnerability of the HIV/AIDS-immunocompromised to opportunistic pathogens are well-documented medical crises [7,[19][20][21][22][23][24][25]. In modeling the interplay between these two health risks, we recently demonstrated that the disrupted selective pressures associated with an HIV/AIDS-related host immunosuppression create the potential for a drastic, AIDS-attributable increase in the novel emergence of drug resistance [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both the emergence of antibiotic resistance and the vulnerability of the HIV/AIDS-immunocompromised to opportunistic pathogens are well-documented medical crises [7,[19][20][21][22][23][24][25]. In modeling the interplay between these two health risks, we recently demonstrated that the disrupted selective pressures associated with an HIV/AIDS-related host immunosuppression create the potential for a drastic, AIDS-attributable increase in the novel emergence of drug resistance [10].…”
Section: Discussionmentioning
confidence: 99%
“…While there is a slight fitness-dependent change in the ratio of drug-sensitive to drug-resistant infections, the rapid q-strain dominance occurs even when its comparative fitness is low. Therefore, surveillance efforts that analyze total tuberculosis (TB) prevalence only, while failing to consider the percentage of resistant strain infectives within the population, could be critically flawed-especially when HIV/AIDS prevalence is high [10].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations